THE DEVELOPMENT OF MARITIME TOURISM AS AN EFFORT TO IMPROVE THE WELFARE - Riana, Nova; Riyanti, Anti (Universitas Pendidikan Indonesia, 2019)
West Java Province has many tourism potencies, consisted of nature, history or culture. In its development, tourism in West Java has not delivered a strategic solution to problematic among the people. Referring to the Legislation of Tourism No.10/2009, one of the principles on tourism establishment is to provide benefit on people’s wealthy and to empower local people. In this study, the locus of Karang Paranje has been chosen by the consideration that Karang Paranje is a potential area to become a tourist destination in coastal and marine for tourists to enjoy nature. Nevertheless, the potencies could not give optimum benefit to people. In aiming the goal, a proper administration is needed, such like building tourism awareness among people about coastal tourism potencies, and the needs of people empowering, building independence that will affect in increasing people’s income. These potencies could be explored as an agenda by Government of Garut Regency to follow up, not to stop at study identifying tourism potencies, but to implement that to be saleable tourism product. The method conducted in this study was exploration qualitative whilst the data gathering used some techniques: observation, questionnaire and in-depth interview, followed by the socialization of the design of tourism development potencies. This study involved some parties such as Government, private sectors (industry), associations, people, and fishermen, so tourism as the leading sector could give a multiplier effect in the community.